Pedagogical implications of figurative language in the movie of Laskar Pelangi: Revisiting the meanings - Veni Nella Syahputri; Nyak Mutia Ismail (Universitas Merdeka Malang, 2023)
This study examines the implications of figurative language in the film adaptation of Laskar Pelangi directed by Riri Riza. Laskar Pelangi is a movie based from a novel by Andrea Hirata which was chosen because of positive messages and motivating storyline it has. The method used to conduct this study was descriptive case study. The data source was merely this 124-minute movie of Laskar Pelangi. The data collection was done through documentation by watching the movies several times to find out the figurative languages and the implications conceived. Later, the data were analyzed using interactive analysis involving data reduction, data display, and data verification. The results show that, first, the literary devices of irony, metaphors, simile, hyperbole, and symbolism are employed in the novel